PENGARUH LAMA SIMPAN DAN LAMA PENCELUPAN DALAM LARUTAN DESINFEKTAN TERHADAP DAYA TETAS TELUR ITIK MOJOSARI (Anas javanica sp.) - Efi Rokhana; Nurfiana . (Universitas Islam Kadiri, 2017)
The purpose of this to know the influence of the old store and the duration of disinfectant to get the best and highest hatchability. The material used in the research were hatching machine, ojosari duck eggs. The method use is RAL 3x3 faktorial with the pattern that produced 9 combination treatment with 5 replicates and produces us experimental units, where each experimental unit consist of eggs, so the total eggs used are 225 research mojosari duck eggsThe result showed the long old store andthe duration of each can be very significant (P<0,01) on the hatcbility, but for long interaction disinfectant store and the duration of effect was not significant (P>0,05) on the hatcbility. Long shelf includes how many days the eggs are stored average is (S1=73%), (S3=81,66%), (S6=75,33%) long immersion include which means that the eggs will be hatched dyed first with disinfectant solution, the average results of research is (C1=73%), (C2=75%), (C3=83%)